Experimental investigation of heat transfer and friction factor of TiO2-SiO2 nanofluids in water:ethylene glycol mixture. (September 2018) - Nabil, M.F.; Azmi, W.H.; Hamid, K.A.; Mamat, R.
Highlights: Heat transfer performance of TiO2 -SiO2 nanofluids under turbulent flow. Experiments are undertaken for different temperature and up to 3% concentration. The maximum heat transfer enhancement was 81% for 3% concentration. The friction factor is slightly increased with concentration insignificantly. The TiO2 -SiO2 nanofluids behaved better performance compared to based fluids. Abstract: This paper introduces the combination of two different nanoparticles suspended in the base fluid for the enhancement of forced convection heat transfer. The aims of the experimental study are to investigate the heat transfer performance and friction factor of TiO2 -SiO2 nanofluids in a circular tube under turbulent flow. The TiO2 -SiO2 nanofluids are prepared by using the two-step method for 0.5 to 3.0% volume concentration with nanoparticle mixture ratio of 50:50. The TiO2 -SiO2 nanoparticles are dispersed in a base fluid of water/EG mixture with a 60:40 volume ratio. The forced convection heat transfer experiment is conducted under working temperatures of 30, 50 and 70 °C and a constant heat flux boundary condition. The heat transfer coefficient of TiO2 -SiO2 nanofluids is enhanced with increase of volume concentration and temperature. It was observed that the maximum enhancement of convective heat transfer is 81% higher than the base fluid for a volume concentration and temperature of 3.0% and 70 °C, respectively. Furthermore, the friction factor of TiO2 -SiO2 nanofluids is slightly increased with volume concentration, however insignificantly. Finally, the regression correlation model of TiO2 -SiO2 nanofluids was developed from the experimental results for the estimation of Nusselt number and friction factor.